Privacy Crisis on Instagram: a Factor Analysis Approach on Motivation Behind Privacy Disclosure in Adolescents - Vivi Varlina; Thesalonika Lefanya Kara Duma (Ikatan Sarjana Komunikasi Indonesia, 2022)
Instagram is one of the most preferred social media platforms in Indonesia. Based on the survey, Instagram users in Indonesia are dominated by teenagers aged between 18 and 24 years. Instagram is used by teenagers as a medium to create self-image, show existence, and do self- disclosure. The disclosure of privacy by teenagers is very risky and has negative impacts, such as provocation, data manipulation, and other cybercrime. This study aims to confirm the factors that motivate teenagers to disclose personal information on Instagram. By using communication privacy management theory and quantitative methodology, this research found interesting insights. Researchers surveyed 100 Instagram users who use public mode accounts. Through a series of factor analyses it was found that out of 17 indicators of the 7 main motivational factors formulated in the initial research framework, only 15 indicators were valid because the significance value of the other 2 indicators did not meet the requirements. These 15 indicators formed 6 new motivational main factors that influence teenagers to disclose their personal information on Instagram. These factors are self-presentation, information storage, emotional support, relationship development, entertainment, and information sharing. This finding also confirmed the novelty of the research that there are some similarities and differences in the factors that motivate Instagram users and Facebook users when disclosing their personal information on both social media platforms.